A pharmacogenomic study revealed an association between SLC6A4 and risperidone-induced weight gain in Chinese Han population. (November 2015) - Wang, Fang; Mi, Weifeng; Ma, Wenbin; Ma, Cuicui; Yang, Yongfeng; Zhang, Hongxing; Du, Bo; Li, Keqing; Liu, Chenxing; Wang, Lifang; Lu, Tianlan; Zhang, Hongyan; et al.
Aim: We carried out a pharmacogenomic study in order to identify susceptible genes for antipsychotics induced weight gain within the Chinese Han population.Materials & methods: We enrolled 216 patients with schizophrenia in our study. All of them underwent risperidone monotherapy, and fulfilled 4-week follow-up. Weight gain was measured before treatment and 4 weeks later. Seven hundred and sixty-eight SNPs from 85 genes were calculated for association with weight gain percentage.Results: Fifty-seven SNPs located at 16 genes with a p-value less than 0.05.4 SNPs located on serotonin transporter gene (solute carrier family 6, member 4, SLC6A4 ) remained significant after multitest correction (rs3813034, p = 0.000357, q = 0.08, rs1042173, rs4325622, rs9303628, p = 0.000451, q = 0.08).Conclusion: SLC6A4 might be susceptible gene for risperidone-induced weight gain within the Chinese Han population.